2022
DOI: 10.1029/2022gl102043
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic Slip Model of the 2022 Mw 6.7 Luding (Tibet) Earthquake: Pre‐ and Post‐Earthquake Interactions With Surrounding Major Faults

Abstract: The 5 September 2022 Mw 6.7 Luding earthquake occurred on the Moxi segment of the highly active Xianshuihe fault in eastern Tibet. Here, we constrain the coseismic slip by jointly inverting the coseismic displacements measured by Global Positioning System, seismometer and Interferometric Synthetic Aperture Radar. Along the Moxi fault, concentrated left‐lateral strike slip extends ∼30 km along the strike above 10 km depth, producing 0.7–1.0 m shallow slip. Clustered aftershocks and slip inversions suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Additionally, our results indicate that the rupture extended up to the top edge of the fault with large shallow slips of about 1 m, situated ∼6 km northwest and 9–16 km southeast of the rupture initiation along the strike direction. This suggests corresponding surface breakages, some of which have been validated by geological field surveys (Li et al., 2022, Figure 3b).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Additionally, our results indicate that the rupture extended up to the top edge of the fault with large shallow slips of about 1 m, situated ∼6 km northwest and 9–16 km southeast of the rupture initiation along the strike direction. This suggests corresponding surface breakages, some of which have been validated by geological field surveys (Li et al., 2022, Figure 3b).…”
Section: Discussionsupporting
confidence: 68%
“…Most of the aftershocks within 1 km from the cross-section CC' to the west of the mainshock's hypocenter become deeper from Point C' to Point C (Figure 2c). The total characteristic of the depth distribution of these aftershocks can tell the main fault dipping southwest, consistent with the main fault with a dip angle of 80° W (Li et al, 2022). To the north, additional unmapped north-west faults intersect with the XSH-F with a rotation angle of about 55° (Figures 2h and 2b).…”
Section: Fault Structurementioning
confidence: 63%
See 1 more Smart Citation
“…The geodetic data set (GNSS and InSAR) provides perfect constraints for shallow slip, but little resolution for downdip slip (Figure S7c in Supporting Information ), similar to the reference of Yanchuan Li et al. (2022). The strong‐motion data can provide good resolution and inversion stability if they are well distributed (Figure S7d in Supporting Information ), consistent with the conclusion yielded by previous studies (Yue & Lay, 2011).…”
Section: Discussionsupporting
confidence: 61%
“…According to prior knowledge and earthquake cases, an earthquake's magnitude that results in a surface rupture on the Chinese mainland is often greater than M 6 3 / 4 (Deng et al, 1992). There were only few kilometers of ambiguous surface rupture from the Luding M 6.8 earthquake in 2022 AD (Li et al, 2022;Han et al, 2023). It is concluded that the 1748 AD Kangding M 6 1 / 2 earthquake may not have Frontiers in Earth Science frontiersin.org produced a surface rupture.…”
Section: Discussionmentioning
confidence: 99%